35‐4: Invited Paper: Physics Based Design Tools. Key to Organic and Oxide Based Thin Film Transistor (oTFT) Technology Innovation?. Issue 1 (2nd June 2017) - Nejim, Ahmed; Mijalkovic, Slobodan; Binder, Thomas; Kelly, Sean
Abstract : Physics based continuous Technology Computer Aided Design (TCAD) models and organic/oxide TFT compact models are key for technology innovation. The encapsulated underlying physics produce predictive models that empower designers to explore all available design space. To achieve this, a number of challenges must be met. These include stable and reproducible fabrication with quantified material parameters. A seamless software flow from TCAD to SPICE opens significant opportunities for future technology designers.